Accidental catheterization of epidural venous plexus: tomographic analysis - Souza,Mariano Paiva (2016)
ABSTRACT BACKGROUND AND OBJECTIVES: Inadvertent venous catheterizations occur in approximately 9% of lumbar epidural anesthetic procedures with catheter placement and, if not promptly recognized, can result in fatal consequences. The objective of this report is to describe a case of accidental catheterization of epidural venous plexus and its recording by computed tomography with contrast injection through the catheter. CASE REPORT: A female patient in her sixties, physical status II (ASA), underwent conventional cholecystectomy under balanced general anesthesia and an epidural with catheter for postoperative analgesia. During surgery, there was clinical suspicion of accidental catheterization of epidural venous plexus because of blood backflow through the catheter, confirmed by the administration of a test dose through the catheter. After the surgery, a CT scan was obtained after contrast injection through the catheter. Contrast was observed all the way from the skin to the azygos vein, passing through anterior and posterior epidural venous plexuses and intervertebral vein. CONCLUSION: It is possible to identify the actual placement of the epidural catheter, as well as to register an accidental catheterization of the epidural venous plexus, using computed tomography with contrast injection through the epidural catheter.